Use of cow dung as shelter by Liolaemus ruibali Donoso-Barros 1961 (Squamata, Liolaemidae) in the Puna region of west-central Argentina - Valdez Ovallez, Franco Miguel (2023)
We found an adult male specimen of Liolaemus ruibali under cow dung (Fig. 1). The individual was captured and wevrecorded its snout-vent length (SVL = 41 mm) and body temperature (16.7 °C). We also recorded the temperature of the substrate under the dung (13.7 °C) and the temperature of the surface of the dung in contact with the substrate (14.3 °C). In addition, we measure the maximum width and length of the dung and calculated its surface area (460 cm2).